Apresente uma derivação à extrema esquerda (DEE) da sentença x = a - (b * c - d) * (d - c / b) - a sobre a gramática a seguir.
G = ({A, B, C, D, E, F, G}, {a, b, c, d, x, =, +, -, *, /, (, )}, P, A)
P = {< A > -> < G > = < B >
< B > -> < D > < C > | < D >
< C > -> + < D > < C > | - < D > < C > | + < D > | - < D >
< D > -> < F > < E > | < F >
< E > -> * < F > < E > | / < F > < E > | * < F > | / < F >
< F > -> ( < B > ) | < G >
< G > -> a | b | c | d | x }
< A >
< G > = < B >
x = < B >
x = < D > < C >
x = < F > < C >
x = < G > < C >
x = a < C >
x = a - < D > < C >
x = a - < F > < E > < C >
x = a - ( < B > ) < E > < C >
x = a - ( < D > < C > ) < E > < C >
x = a - ( < F > < E > < C > ) < E > < C >
x = a - ( < G > < E > < C > ) < E > < C >
x = a - ( b < E > < C > ) < E > < C >
x = a - ( b * < F > < C > ) < E > < C >
x = a - ( b * < G > < C > ) < E > < C >
x = a - ( b * c < C > ) < E > < C >
x = a - ( b * c - < D > ) < E > < C >
x = a - ( b * c - < F > ) < E > < C >
x = a - ( b * c - < G > ) < E > < C >
x = a - ( b * c - d ) < E > < C >
x = a - ( b * c - d ) * < F > < C >
x = a - ( b * c - d ) * ( < B > ) < C >
x = a - ( b * c - d ) * ( < D > < C > ) < C >
x = a - ( b * c - d ) * ( < F > < C > ) < C >
x = a - ( b * c - d ) * ( < G > < C > ) < C >
x = a - ( b * c - d ) * ( d < C > ) < C >
x = a - ( b * c - d ) * ( d - < D > ) < C >
x = a - ( b * c - d ) * ( d - < F > < E > ) < C >
x = a - ( b * c - d ) * ( d - < G > < E > ) < C >
x = a - ( b * c - d ) * ( d - c < E > ) < C >
x = a - ( b * c - d ) * ( d - c / < F > ) < C >
x = a - ( b * c - d ) * ( d - c / < G > ) < C >
x = a - ( b * c - d ) * ( d - c / b ) < C >
x = a - ( b * c - d ) * ( d - c / b ) - < D >
x = a - ( b * c - d ) * ( d - c / b ) - < F >
x = a - ( b * c - d ) * ( d - c / b ) - < G >
x = a - ( b * c - d ) * ( d - c / b ) - a